2007
DOI: 10.1080/08923970701513443
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen Peroxide on Interleukin-8 Synthesis and Death of Caco-2 Cells

Abstract: Intestinal epithelial cells can secrete interleukin-8 (IL-8), among other substances in response to different stimuli, which plays an important role in mucosal immune response. Above a certain concentration range, hydrogen peroxide causes cell death by necrosis or apoptosis. We investigated the time- and dose-dependent induction of IL-8 by hydrogen peroxide in the human colon adenocarcinoma cell line Caco-2. In addition, the changes of transepithelial electrical resistance and cell death induction in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…It should be noted that we observe a continuous cell monolayer after H 2 O 2 exposure, up to concentrations of 50 mM (immunofluorescence staining, data not shown). This is in agreement with reports in the literature that observe TER disruption on addition of modest amounts of H 2 O 2 (10–40 mM), without gross disruption of monolayer integrity 25, 26. Permeability assays after exposure to ethanol indicate that barrier properties are disrupted for concentrations over 20%.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It should be noted that we observe a continuous cell monolayer after H 2 O 2 exposure, up to concentrations of 50 mM (immunofluorescence staining, data not shown). This is in agreement with reports in the literature that observe TER disruption on addition of modest amounts of H 2 O 2 (10–40 mM), without gross disruption of monolayer integrity 25, 26. Permeability assays after exposure to ethanol indicate that barrier properties are disrupted for concentrations over 20%.…”
supporting
confidence: 92%
“…Experiments discussed here were performed using complete cell culture media as the delivery vehicle. The fact that the OECT operates so well in such a complex environment is an advantage, and we believe that we are sensing a more subtle disruption of barrier tissue than previously demonstrated 25. Figure 3d shows apparent permeability data of Caco‐2 layers exposed to H 2 O 2 and ethanol, in complete cell culture media.…”
mentioning
confidence: 86%
“…Studying the early effects of H 2 O 2 on filter-grown Caco-2 cells, it was found that 1-4 mM H 2 O 2 had no impact on cell viability, whilst 20% of nuclei were stained with DAPI after 10 mM H 2 O 2 exposure, indicating cell necrosis. IPEC-J2 cells seem to be more sensitive since 10% and 15% of the IPEC-J2 cells became necrotic after 2 and 4 mM H 2 O 2 treatment, respectively [26]. The decrease in TER may reflect an increase in the movement of solutes and ions across the epithelium by transcellular pathways.…”
Section: Discussionmentioning
confidence: 98%
“…They secrete cytokines and chemokines due to adverse stimuli such as oxidative stress. IEC were proven to produce IL-8 in response to H 2 O 2 in vitro [4][5][6]26]. All these studies were performed with human carcinoma-derived cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The apical junction is responsible for the regulation of ions and molecules passing across the barrier 5,6 via a specific opening and closing function. A dysfunction or disruption of these protein complexes is often related to disease [7][8][9][10][11] . In addition, many enteric pathogens/ toxins are known to specifically target this complex, thereby entering the body and leading to diarrhea, most likely as a consequence of massive dysregulation of ion/water flow across the barrier [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%